PERBAIKAN KUALITAS PROSES PHYLON DENGAN METODE SEVENTOOLS DAN PDCA DI PT KGS - Yusuf, Muhammad (Teknologi : Jurnal Ilmiah dan Teknologi, 2025)
The presence of rejected products in the Phylon Injection departement in PT KGS is still considered by the negligence of Workers, Methode, Machine, Materials and the Environment that cause company losses because the company must reproduce to replace reject products. The research was conducted to determine and analyze the level of defective products that occurred during 2022 and 2023, find out the highest types of reject, and know the factors causing these defective products. The results of the analysis using the Pareto Diagram of rejecting in 2022 and 2023 were 171.164 pcs, and the highest reject was produced by burning, namely 58.414 pcs, of other types of reject, namely bubbles as many as 47.936 pcs, dirty as many as 37584 pcs, deformed as many as 14.770 pcs, hole as 8513 pcs and tearing as many as 3.947 pcs. The highest reject histogram was burning, which was 112353 pcs, and the Control Chart had p values out of UCL and LCL, which means that the perdefect rate exceeded the control limit. Based on the results of the analysis using the seven tools method, it can be concluded that the seven tools method can find out the problems that are happening at PT KMK Global Sport.